Ciało złe i dobre. Kwestia pochodzenia i natury ciała Adama i Chrystusa we wczesnochrześcijańskich ruchach heretyckich - Szram, Mariusz (Vox Patrum, 2015)
The article expounds on the groundwork laid by the first Latin treaty De haeresibus by Philastrius, the fourth-century bishop of Brescia, analyzed on the background of writings of Irenaeus, Tertullian and Origen, how the rooted in Gnosticism representatives of early Christian heresies (Carpocratians, Saturninus, Valentinus, Apelles, Marcion, Manicheans) have comprehended the genesis of man’s body. After a general delivery of early Christian doubts regarding the value of human flesh, different varieties of heretical paradox – ensuing from Platonic and Gnostic cosmo-anthropological tendencies – are presented. The paradox could be formulated in the following manner: human body of the first man Adam – and correspondingly all of his descendants – is genetically and ontologically evil as being an elementary constituent of the material world. Hence the flesh of a new Adam, i.e. Christ, must come form another realm and be free of the earthly materiality in order to be good by nature and worthy of Saviour’s person. The presented mode of thinking instigated the rise of theological misconceptions, in particular the eschatological ones denying human body the possibility of resurrection and recognizing – in a Gnostic fashion – the liberation of man from flesh, not his salvation alongside his body.